2017
DOI: 10.2147/cia.s142341
|View full text |Cite
|
Sign up to set email alerts
|

A scoping review of crisis teams managing dementia in older people

Abstract: BackgroundResearch on crisis teams for older adults with dementia is limited. This scoping review aimed to 1) conduct a systematic literature review reporting on the effectiveness of crisis interventions for older people with dementia and 2) conduct a scoping survey with dementia crisis teams mapping services across England to understand operational procedures and identify what is currently occurring in practice.MethodsFor the systematic literature review, included studies were graded using the Critical Apprai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(48 citation statements)
references
References 16 publications
1
47
0
Order By: Relevance
“…An additional scoping survey of TMCDs in the UK was undertaken to provide a picture of current TMCD service delivery. Results of the systematic review and scoping survey are published elsewhere [5].…”
Section: Systematic Review and Scoping Surveymentioning
confidence: 99%
See 2 more Smart Citations
“…An additional scoping survey of TMCDs in the UK was undertaken to provide a picture of current TMCD service delivery. Results of the systematic review and scoping survey are published elsewhere [5].…”
Section: Systematic Review and Scoping Surveymentioning
confidence: 99%
“…This is underpinned by a desire to maintain and enhance independence for people with dementia, in order to improve their quality of life and that of their carers [2], and to reduce the financial costs associated with admission to acute settings [3,4]. Specific community-based services, typically operating within a Home Treatment Team model, exist to support people with dementia and their carers during times of crisis when the ability to remain independent is compromised and an admission to hospital is a likely outcome [5]. Such situations often arise due to a change or deterioration in physical and/or mental health function of the person with dementia, or a breakdown in care being provided by either formal or informal carers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…25,26 However, the evidence for innovative mental health care strategies for elderly people is scarce. 27 Most studies using ACT, [28][29][30] HT, [31][32][33][34][35] or CRT [36][37][38] did not specifically report whether the innovative care models reduced AHLS in geriatric populations with mental health care needs. A British study showed that CRT and HT significantly reduced admissions of elderly mentally ill patients, but there was no significant difference in AHLS as compared before and after the introduction of these services.…”
Section: Procedures In Medicine Of the World Health Organization Calledmentioning
confidence: 99%
“…Speci c community-based services exist to support people with dementia and their carers during times of crisis when their ability to remain independent is compromised and inpatient admission to hospital likely . Referral routes to these services vary, and service models include: stand-alone crisis services, often called Crisis Home Treatment Teams, or crisis services embedded within community services with a broader remit, such as community Mental Health Teams or Memory Assessment Services (5). Such situations often arise due to a change or deterioration in physical or mental health function of the person with dementia, or a breakdown in care .…”
Section: Introductionmentioning
confidence: 99%